Answer:
y=2x+6.
Explanation:
1) the condition 'an x-intercept of "-3"' means the point A with the coordinates (-3;0), then it is possible to make up the required equation according to the rule (the coordinates (-2;2) belong to the point B):
![2) \ (x-X_B)/(X_A-X_B)=(y-Y_B)/(Y_A-Y_B), \ where \ X_A=-2;Y_A=2;X_B=-3;Y_B=0.](https://img.qammunity.org/2022/formulas/mathematics/college/dyjl6l2xrmnilnfbonvd0x7rgcomvlkcjb.png)
after the substitution the coordinates into the rule:
![(x+3)/(-2+3) =(y-0)/(2-0); \ => \ (x+3)/(1)=(y)/(2); \ => \ y=2x+6.](https://img.qammunity.org/2022/formulas/mathematics/college/cksonvwgcban021ljqjmxn8t7gr1i223q3.png)